Relationship of Objectively Measured Physical Activity, Sedentary Behavior and Sleep Time with Cardiovascular and Mtabolic Outcomes in Adolescents (A Pilot Study): ABCD Growth Study - Wigna, Andrea [UNESP]; Urban, Jacqueline B [UNESP]; Torres, Wésley [UNESP]; Moraes-Chagas, Lucas G [UNESP]; Dias, Jefferson S [UNESP]; Nunes, David S [UNESP]; de-Menezes, Veronica A [UNESP]; Fernandes, Rômulo A [UNESP] (Springer Nature, 2022)
Study objective: Different behaviors are considered important factors that may influence a healthy lifestyle. Given this fact, we aim to analyze the relationship between moderate-vigorous physical activity (MVPA), sleep time, and sedentary time, with cardiometabolic outcomes in adolescents. Methods: Cross-sectional study, with 152 eutrophic and healthy adolescents. The behavioral variables were collected objectively and the arterial thickness was measured through ultrasound. Blood variables (LDL, TG, HDL, glucose, and insulin) were collected in a private laboratory. To analyze the data, the Student t test and Kruskal-Wallis test were used to compare the groups. All analyses adopted p < 0.05. Results: Girls who demonstrated better combined behaviors, presented significant results for TG (p = 0.045), BP (p = 0.016), and cardiovascular score (p = 0.049) when compared to their peers. Furthermore, the practice of physical activity combined with sufficient sleep time was associated with lower values of arterial thickening (p = 0.017). Conclusions: In view of the results presented, it is possible to state that the aggregation of behaviors was more consistent in females and that the practice of physical activity and adequate sleep time can reflect on cardiovascular health.
Keywords: Adolescents; Physical Activity; Risk Factors